Finite element simulation of electro-mechanical impedance technique - Tahmasebpour, Kamyar; Hrairi, Meftah; Shaik Dawood, Mohd. Sultan Ibrahim (2015)
Electro-mechanical impedance method is emerging as an important and powerful technique for structural health monitoring (SHM). Active elements of the technique are Piezoelectric Wafer Active Sensor (PWAS) bonded on the structure. Modeling and simulation of PWAS and host structure play an important role in the SHM applications with PWAS. For decades finite element method has been extensively applied in the analysis of piezoelectric materials and structures. In this paper, piezoelectric element and a host metallic structure were modeled using Ansys finite element software to find the Electromechanical Impedance (EMI) according to the signal frequency. After that, the EMI signature of the beam was found for different position of the PWAS patch. The study shows that sensor position may directly control the EMI signature.